Taxing Policy Reconstruction Based on Justice Value to Encourage Industrial Competitiveness in the Global Era - Amin Purnawan (International Journal of Law Reconstruction, 2017)
The study of trading will not be separated from the study of industry and investment, they have the close relationship of these three things in determining the competitiveness of a country, especially in the current pattern of global value chain (GVC) trading. The aims of this study are: (a) to analyze the urgency of increasing the competitiveness of national industry in the era of world free trade, and (b) to reconstruct taxation policies to promote industrial competitiveness in the global era. Tax reform should be able to improve competitiveness, and enthusiasm to invest for the investors. Due to growing business will increase tax revenue. The tax policy is very influential on industry, trade, and investment, because according to business people, tax is the biggest investment constraint, besides security, law, labor, regional autonomy, and smuggling issue. The reconstruction of taxation policies through the updating of tax laws includes: simplifying administrative procedures, raising taxpayer awareness, implementing a credible, accountable and consistent self-assessment system, tariffing adjustments to improve competitiveness, and expanding tax bases to increase state revenues. In order to improve competitiveness with other countries, it is necessary to put forward the principles of fairness and neutrality in tariff setting, and provide incentives for small business development. The structure of the prevailing tax rate is simplified in stages, planned, differentiated tariffs, and simplified layers intended to provide a more proportional tax burden for each taxpayer class.